Pengaruh Media Iklan Terhadap Keputusan Membeli Air Minum dalam Kemasan Merk Lam-Lam pada Masyarakat Kota Bima - Nurjoko, Hadi; Putra, Nyoman Nugraha Ardana; Pribadi, Benny Agus (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
The aim of this research is to analyze the influence of online and offline advertising media on decision making to purchase Lam-Lam brand bottled drinking water among the people of Bima City. The research population was all buyers of Lam-Lama mineral drinking water in Bima City, and 53 consumers were used as research samples. The research instrument was a questionnaire using a Likert scale, and the data was analyzed using multiple linear regression analysis techniques. The research results show that the use of online advertising media has a positive and significant influence on the decision of buyers of the Lam-Lam brand of mineral water in Bima City. The use of offline advertising media has a positive and significant effect on the decision of buyers of the Lam-Lam brand of mineral water. The use of online and offline advertising media has a simultaneous and significant influence on the decisions of buyers of Lam-Lam mineral water. The implication of this research is that companies can continuously carry out marketing activities online and offline in a balanced manner so that the product image is increasingly trusted by consumers.